FARMER’S NEED ASSESSMENT FOR HYBRID PADDY AND FACTORS INFLUENCING THE PURCHASE DECISION - P. RADHIKA, K. ANIL, SEEMA and (The Journal of Research, PJTSAU, 2019)
Hybrid rice technology is likely to play a key role in increasing the rice production. During the year 2008, hybrid rice was planted in an area of 1.4 m.ha and an additional rice production of 1.5 to 2.5 m.t. (Directorate of Rice Research, 2014) was added to our food basket through this technology. More than 80 per cent of the total hybrid rice area is in Eastern Indian states like Uttar Pradesh, Jharkhand, Bihar, Chattisgarh, with some little area in states like Madhya Pradesh, Assam, Punjab and Haryana. As rice is a key source of livelihood in Eastern India, a considerable increase in yield through this technology will have a major impact on household food and nutritional security, income generation, besides an economic impact in the region. In view of this, hybrid rice has been identified as one of the components under the National Food Security Mission (NFSM) launched by the Government of India (GOI) with the aim to enhance rice production by 10 m.t. by 2011-12. Similarly, added emphasis is being given for adoption of hybrid rice under the special scheme of GOI to bring green revolution to Eastern India.